Early emotional caregiving environment and associations with memory performance and hippocampal volume in adolescents with prenatal drug exposure - Kohn, Brooke H.; Cui, Zehua; Candelaria, Margo A.; Buckingham-Howes, Stacy; Black, Maureen M.; Riggins, Tracy (Frontiers in Behavioral Neuroscience, 2023)
Early adversities, including prenatal drug exposure (PDE) and a negative postnatal emotional caregiving environment, impact children’s long-term development. The protracted developmental course of memory and its underlying neural systems offer a valuable framework for understanding the longitudinal associations of pre- and postnatal factors on children with PDE. This study longitudinally examines memory and hippocampal development in 69 parent–child dyads to investigate how the early caregiving emotional environment affects children with PDE’s neural and cognitive systems. Measures of physical health, drug exposure, caregiver stress, depression, and distress were collected between 0 and 24 months At age 14 years, adolescents completed multiple measures of episodic memory, and at ages 14 and 18 years, adolescents underwent magnetic resonance imaging (MRI) scans. Latent constructs of episodic memory and the caregiving environment were created using Confirmatory Factor Analysis. Multiple regressions revealed a negative emotional caregiving environment during infancy was associated with poor memory performance and smaller left hippocampal volumes at 14 years. Better memory performance at 14 years predicted larger right hippocampal volume at 18 years. At 18 years, the association between the emotional caregiving environment and hippocampal volume was moderated by sex, such that a negative emotional caregiving environment was associated with larger left hippocampal volumes in males but not females. Findings suggest that the postnatal caregiving environment may modulate the effects of PDE across development, influencing neurocognitive development.